Revitalizing Nature’s Meaning in “Jabbaratul Ghabah” Short Story by Kamil Kailani: Shklovsky's Defamiliarization Study - Wananda, Anida Shofiyah; Halimi, Halimi (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2025)
The impact of unusualness in literature is frequently employed by authors to create distinctive literary works. One technique that facilitates this uniqueness is defamiliarization. The objective of this study is to identify various defamiliarization techniques utilized by Kamil Kailani in his narrative and to elucidate the concept of natural revitalization as conveyed through the interactions between characters and nature in the short story